Heavy metal pollution in water and soil and associated health risks in a tin mining region of Hunan Province, Central China - Lan Wang; Jian-feng Li; Xiu-wen Liu; Li-xiao Feng (China Geology, 2025)
ABSTRACT: To assess the effect of mining activity on heavy metal pollution and associated health risks in tin mining regions, water and soil sampling was conducted near a tin mining site in Hunan Province. The content and distribution of heavy metals were determined. Pollution, ecological risks, and potential health hazards were evaluated using the ground accumulation index, potential ecological risk index, and health risk assessment models, respectively. The results indicated elevated levels of heavy metals in water and soil samples compared to acceptable background values. Ground accumulation index assessment revealed extreme pollution of soil with As and Cd and moderate pollution with Cu, Pb, and Zn. Cr and Hg were categorized as non-pollutants. Water samples exhibited extreme pollution levels of Hg, Cr, Cd, and As; moderate pollution levels of Pb; and moderate to high pollution levels of Cu and Zn. The tin mining area demonstrated a significantly high level of potential ecological risk, where As and Cd were the primary risk elements in soil, whereas Cr, Cd, and As contributed predominantly to water ecological risk. The human health risk assessment highlighted As, Cd, Cr, Hg, Pb, and Cu in water and As and Pb in soil as the principal non-carcinogenic factors. The primary carcinogenic factors were As, Cr, and Cd in water and As in soil, with As posing the greatest risk for non-carcinogenic and carcinogenic effects. Furthermore, oral intake was the primary exposure route, with children being particularly vulnerable to the adverse effects of heavy metal pollution.